Eksperimen tumbukan: analisis kecepatan benda setelah terjadi tumbukan - Muthiah, Zaeda Nihayatul (Maliki Interdisciplinary Journal, 2026)
conservation of linear momentum and kinetic energy. The method used was a laboratory experiment employing an air track, gliders, a blower, and photogate sensors to measure time and velocity before and after collisions. The experiment was conducted under several conditions, namely one object initially at rest and both objects in motion, with variations in equal and unequal masses. Velocity data were obtained from time measurements and subsequently used to calculate the momentum of each object. The experimental results show that the law of conservation of linear momentum holds for a closed system in the absence of external forces. However, kinetic energy is not always conserved and only remains constant in perfectly elastic collisions. Differences between experimental results and theoretical calculations are attributed to instrument limitations, residual friction, and inaccuracies during data collection. Thus, this experiment demonstrates that the principles of collisions and momentum can be experimentally observed and are consistent with fundamental physics theory.